Research in English for communication - Razali, Khairil Azwar (Kulliyyah of Languages & Management (KLM), International Islamic University Malaysia, 2020)
This book is a collection of research reports on the areas related to English for Communication. The book attempt to highlight certain issues that are considered as critical in English for Specific Purposes. The topics discussed in this book are semantic (taboo words), translation study of fan-made scanlation of Japanese manga, conversation analysis on WhatsApp messages, motivation and attitudes towards learning English, and also on employers’ perceptions on what is considered as good communication skills. This book does not only highlight the subject contents, but also methodologies used within English for Communication field.